Analisis paparan karbon monoksida (CO) dengan keluhan subjektif pernapasan pada penjual satai di Kota Duri tahun 2023 - Veronica, Yohana; Nurmaini; Chahaya, Indra; Indirawati, Sri Malem (TROPHICO: Tropical Public Health J., 2024)
Nowadays, buying food from outside is one of the choices people make when busy. Satai is one of the culinary favorites of many people. Many people are not aware and do not know that the process of burning satai involving carbon materials in the form of charcoal can produce smoke containing carbon monoxide which is risky for buyers and sellers. The smoke produced from burning satai contains carbon monoxide, making satai sellers a profession that is very at risk of subjective respiratory complaints. A preliminary survey found that 6 out of 10 satai sellers in Duri City experienced subjective respiratory complaints due to smoke from burning satai. The purpose of this study was to analyze the exposure to carbon monoxide concentrations with subjective respiratory problems among satai sellers. This research uses a cross-sectional approach. Sampling was utilized using a research sample of 40 respondents. The study found that the variables associated with subjective respiratory complaints were carbon monoxide concentration (p=0.010) and work period (p= 0.023). The unrelated variables are body mass index (p= 0.412), length of exposure (p= 0.182), and smoking behavior (p= 0.608). The recommendation offered to satai vendors is to get used to using Personal Protection Equipment (PPE), take out lung health checks, implement shifting tasks, eat lots of drinking water, and pay attention to working hours and the distance between the seller and the satai burning location.